1976
DOI: 10.1029/gl003i012p00754
|View full text |Cite
|
Sign up to set email alerts
|

Precision leveling with a two‐fluid tiltmeter

Abstract: Thermally induced errors, dominant in a water‐tube tiltmeter, are eliminated by using two adjacent tubes containing fluids with densities having different temperature coefficients. Simultaneous measurements of the apparent difference in height between two stations indicated by the two fluids are used to provide the required correction for the density changes. The application of this method could allow precise measurements over long baselines (a resolution of about 10−8 to 10−9 radians in a 1‐kilometer instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Both are capable of high resolution (10~8 rad) and low drift (1.5 microrad/year). Hugget and Slater (1976) describe a relatively simple physical means of compensating for temperature differences along the baseline. Serata has developed a practical liquid level meter which measures vertical displacement between two points connected by a liquid line with a resolution equal to that cf the LVDT device (10 -4 * 10" 6 in) used to measure the liquid level.…”
Section: Stress Measurements-stress Measurement In Saltmentioning
confidence: 99%
“…Both are capable of high resolution (10~8 rad) and low drift (1.5 microrad/year). Hugget and Slater (1976) describe a relatively simple physical means of compensating for temperature differences along the baseline. Serata has developed a practical liquid level meter which measures vertical displacement between two points connected by a liquid line with a resolution equal to that cf the LVDT device (10 -4 * 10" 6 in) used to measure the liquid level.…”
Section: Stress Measurements-stress Measurement In Saltmentioning
confidence: 99%
“…In short fluid tube tiltmeters (•< 100 m) it is frequently possible to control the physical conditions of the tube, but in a long instrument near the earth's surface the thermally induced noise can cause significant errors in the measured tilt signal unless ways to overcome thermal influences are introduced. Michelson [1914] used a horizontal half-filled tube with a continuous water-air interface, and recently, Huggett et al [1976] have suggested a method for reducing the temperature effects in a fluid level type tiltmeter by the use of two fluids of different expansion coefficients in thermal contact.…”
Section: Introductionmentioning
confidence: 99%
“…Huggett, Slater, and Pavlis [5] proposed a two-fluid scheme using differential temperature coefficient fluids to correct for the temperature.…”
Section: U-tube Errormentioning
confidence: 99%
“…Applications requiring this degree of precision are typically limited to geophysics [4,5,6], accelerator alignment [7,8,9,10,11], and recently a radio telescope [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%